Pengaruh Teknik Relaksasi Nafas Dalam Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi Di Desa Pauh Barat Wilayah Kerja Puskesmas Pariaman Tahun 2023 - Fajri Febrini Aulia; Sri Ameliati (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2023)
Hypertension in Indonesia is the number 3 (three) cause of death, after stroke and tuberculosis. Hypertension is more dominated by the elderly. Management for hypertension can be non-pharmacological with deep breath relaxation techniques. Uncontrolled hypertension will lead to further complications such as heart disease, kidney failure and stroke. The purpose of the study was to determine the effect of deep breath relaxation techniques on lowering blood pressure in patients with hypertension in the Pariaman Health Center working area. This research is quantitative, experimental research type. The research was conducted at the Pariaman Health Center in 12 June to 14 June 2023. The sample in this study were 20 elderly people with hypertension. The results of the study found that the average blood pressure of patients before being given the deep breath relaxation technique was 150.95 / 86.20 mmHg. The average blood pressure of patients after being given deep breath relaxation techniques is 145.40 / 80.70 mmHg. There is an effect of deep breath relaxation techniques on lowering blood pressure in hypertensive patients in the Pariaman Health Center work area with a p value of 0.000. In addition to applying pharmacological therapy to patients with hypertension, it is recommended that the health center, especially doctors, be able to provide advice to outpatients with hypertension who visit in order to carry out non-pharmacological therapy in the form of deep breath relaxation techniques as an additional therapy to lower blood pressure.